Multi-omics elucidates the kidney damage caused by aquatic Cu via the gut-kidney axis in ducks - Mingcai Duan; Jinyu Liu; Zhaoxia Cai; Li Chen; Yong Tian; Wenwu Xu; Tao Zeng; Tiantian Gu; Lizhi Lu (Ecotoxicology and Environmental Safety)
Copper (Cu) is an essential trace element for biological growth and development. Excessive intake of Cu exists harmful effects on organisms. However, whether excessive Cu intake induces kidney function damage by gut microbiota regulation remains unclear. Ducks are important species of waterfowl that are often exposed to Cu contamination in water sources. In this study, we aim to elucidate the effects of Cu exposure on renal inflammation through the gut-kidney axis in ducks. The ducks were gavaged with different doses of CuSO4 (0, 100, and 200 mg/kg body weight) for 4 weeks. Results indicate that Cu exposure causes pathological damage to the kidney, with a significant increase in the levels of TNFα, IL-6, and IL-1β in both serum and renal tissue. 16S rDNA analysis revealed that the relative abundances of Candidatus_Saccharimonas and Bacteroides were significantly reduced in the Cu-induced group. Transcriptomic analysis of kidney tissue reveals that following Cu exposure, 30 genes show significant differential expression. GO and KEGG enrichment analyses were most involved in Interleukin-1 Receptor Activity, Taurine and hypotaurine metabolism, Nitrogen metabolism, and Proximal tubule bicarbonate reclamation. Metabolomic analysis revealed that 28 metabolites are present in both kidney tissue and cecal contents. Correlation analysis revealed a strong correlation among 5 common metabolites: Aminoglutethimide, Boscalid, Dantrolene, Cer[ns] d34:1, and Stearidonic acid. In the cecum, these five metabolites are closely associated with 26 intestinal microorganisms, including Bacteroides, Candidatus_Saccharimonas, and Colidextribacter. In the kidney, apart from Stearidonic acid, the other four metabolites are closely correlated with genes such as FOS, and IL1RL1. Overall, our study indicates that excessive Cu induces significant kidney inflammation, the metabolites alteration and gut microbiota disorders. These findings shed light on the underlying mechanisms of Cu-induced kidney damage via the indirect pathway of the gut-kidney axis.